CD4+FOXP3+ Regulatory T Cell Therapies in HLA Haploidentical Hematopoietic Transplantation - Mancusi, Antonella; Piccinelli, Sara; Velardi, Andrea; Pierini, Antonio (Frontiers in Immunology, 2019)
Since their discovery CD4+FOXP3+ regulatory T cells (Tregs) represented a promising tool to induce tolerance in allogeneic hematopoietic cell transplantation. Preclinical models proved that adoptive transfer of Tregs or the use of compounds that can favor their function in vivo are effective for prevention and treatment of graft-versus-host disease (GvHD). Following these findings, Treg-based therapies have been employed in clinical trials. Adoptive immunotherapy with Tregs effectively prevents GvHD induced by alloreactive T cells in the setting of one HLA haplotype mismatched hematopoietic transplantation. The absence of post transplant pharmacologic immunosuppression unleashes T-cell mediated graft-versus-tumor effect, which results in an unprecedented, almost complete control of leukemia relapse in this setting. In the present review, we will report preclinical studies and clinical trials that demonstrate Treg ability to promote donor engraftment, protect from GvHD and improve graft-versus-tumor effect. We will also discuss new strategies to further enhance in vivo efficacy of Treg-based therapies.